Tell Us How We are Doing : Motivating Teams Through Feedback Versus Public Recognition - Delavallade, Clara (World Bank, Washington, DC, 2021)
Motivating service providers to improve the quality of public service delivery is a major development challenge across the globe. This is particularly relevant for women, who are over-represented as providers of essential public services such as healthcare and education in Africa. In the context of a national school nutrition program in the Western Cape province of South Africa, the authors offered either private feedback or public recognition to female school-feeding teams to examine the effectiveness of different incentives schemes when financial rewards are not available. Receiving private feedback on performance boosted workers’ effort more than public recognition. These results suggest that providing performance feedback can be an effective policy for motivating female teams and improving service delivery, more so than mechanisms leveraging public image.